IMPROVING STUDENTS’ STORYTELLING ABILITY BY USING STICK PUPPET AND JIGSAW TECHNIQUE - Widiyanti, Rahmi; Rosnija, Eni; Salam, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract : This research was conducted on 8A students of SMP Mujahidin Pontianak in academic year 2012/2013. The purpose of this research was to improve students’ storytelling ability by using Stick Puppet and Jigsaw technique. The problem found in this research was students’ difficulties in retelling setting, characters, conflict, solution, and moral value of a story. Therefore, to overcome the problem, the researcher designed a classroom action research by using Stick Puppet and Jigsaw technique. The classroom action research was conducted in three cycles. Each of the cycles began with planning, acting, observing, and reflecting stage. In collecting the data, the researcher used close-ended questionnaires, observation checklists and field notes to record the process in the classroom; and performance test to measure students’ storytelling performance. Based on the research finding, students’ storytelling ability improved from first to third cycles. From this result, action hypothesis that stick puppet and jigsaw technique can improve students’ storytelling ability to 8A students of SMP Mujahidin in academic year 2012/2013 was accepted. Keywords : Storytelling, stick puppet, jigsaw technique Abstrak : Penelitian ini dilakukan pada siswa 8A SMP Mujahidin Pontianak Tahun Ajaran 2012/2013. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan siswa dalam bercerita kembali dengan menggunakan boneka tongkat dan tekhnik Jigsaw. Masalah yang ditemukan dalam penelitian ini adalah kesulitan siswa dalam menceritakan kembali latar, tokoh, konflik, solusi konflik, dan nilai moral dari sebuah cerita. Oleh karena itu, peneliti merancang sebuah penelitian tindakan kelas dengan menggunakan boneka tongkat dan tekhnik jigsaw. Penelitian ini dilaksanakan dalam tiga siklus. Setiap siklus dimulai dengan tahapan perencanaan, pelaksanaan, observasi, dan refleksi. Dalam pengumpulan data, peneliti menggunakan kuesioner terutup, lembar pengamatan dan catatan lapangan untuk menceritakan proses yang terjadi di dalam pembelajaran, serta tes penampilan untuk menilai penampilan bercerita kembali dari siswa. Berdasarkan temuan, kemampuan siswa dalam bercerita kembali meningkat dari siklus pertama hingga siklus ketiga. Dari hasil ini disimpulkan bahwa hipotesis tentang penggunaan boneka tongkat dan teknik jigsaw terbukti dapat meningkatkan kemampuan siswa dalam bercerita kembali. Kata kunci : Bercerita kembali, Boneka tongkat, tekhnik jigsaw